Dynamic MR angiography in acute aortic dissection. Issue 2 (28th November 2014) - Kinner, Sonja; Eggebrecht, Holger; Maderwald, Stefan; Barkhausen, Jörg; Ladd, Susanne C.; Quick, Harald H.; Hunold, Peter; Vogt, Florian M.
<x xml:space="preserve">Abstract</x> Background To evaluate the benefit (additional flow information), image quality, and diagnostic accuracy of a dynamic magnetic resonance angiography (MRA) combining high spatial and temporal resolution for the preinterventional assessment of acute aortic dissection. Methods Nineteen patients (12 men, 7 women; aged 32–78 years) with acute aortic dissection underwent contrast‐enhanced four‐dimensional (4D) MRA and 3D conventional high‐resolution MRA (3D MRA) within one examination on a 1.5 Tesla MR system. Both MRA datasets for each patient were evaluated and compared for image quality and visualization of vascular details on a 5‐point scale (5 = excellent image quality, 1 = nondiagnostic image quality). In addition, presence and relevance of additional hemodynamic information (flow direction and organ perfusion delay) gained by dynamic MRA were assessed. Results Conventional 3D MRA provided significantly higher values for image quality of the aorta and aortic side branches compared with dynamic MRA (aorta: 4.3 versus 3.3; P = 0.006 side branches: 4.2 versus 3.3; P = 0.02). However, in 10 of the 19 patients (53%) the additionally available information on flow dynamics due to dynamic MRA (e.g., delayed perfusion of parenchymal organs) led to a change in therapy planning and realization. Conclusion Dynamic MRA is a technique that combines functional flow and morphological information. Thus, the combination of 3D and dynamic MRA provides all requested information for treatment planning in patients suffering from acute aortic dissection. J. Magn. Reson. Imaging 2015;42:505–514.